ANALISIS KEMAMPUAN PEMAHAMAN KONSEPTUAL SISWA KELAS III MADRASAH IBTIDAIYAH SWASTA (MIS) SAKSI TANJUNGBALAI DALAM KLASIFIKASI BANGUN DATAR - Anim Anim; Aidilla Fitria Sari Siregar; Hera Azhari Bangun; Nurlia Ningsih; Andy Sapta (Smart Education, 2026)
Abstract: This study aims to describe the conceptual understanding ability of third-grade students at MIS Saksi in classifying two-dimensional shapes (flat shapes). Mathematics at the elementary school level is often considered difficult due to its abstract nature, particularly in geometry. This research employs a descriptive qualitative approach to explore how students recognize, group, and understand the characteristics of flat shapes through real objects. The subjects of the study were 25 third-grade students who are in the concrete operational stage of development. The research instrument consisted of an evaluation test measuring the ability to elaborate on concepts, present examples, and perform independent articulation. The results showed that 40% of students were in the high category, 32% in the medium category, and 28% in the low category. Students in the high category were able to connect concepts with concrete objects around them and explain the properties of flat shapes in their own words. Meanwhile, the main obstacle for students in the low category was difficulty in understanding question instructions and mathematical literacy. Overall, the majority of students (72%) have achieved fair to excellent understanding in the classification of flat shapes. Keywords: Conceptual Understanding, Two-Dimensional Shapes, Geometry, Elementary School, Classification. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemampuan pemahaman konseptual siswa kelas III MIS Saksi dalam mengklasifikasikan bangun datar. Matematika di tingkat sekolah dasar seringkali dianggap sulit karena sifatnya yang abstrak, terutama pada materi geometri. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk menggali bagaimana siswa mengenali, mengelompokkan, dan memahami ciri-ciri bangun datar melalui objek nyata. Subjek penelitian terdiri dari 25 siswa kelas III yang berada pada tahap perkembangan operasional konkret. Instrumen penelitian berupa tes evaluasi yang mengukur kemampuan menguraikan konsep, penyajian contoh, dan artikulasi mandiri. Hasil penelitian menunjukkan bahwa 40% siswa berada pada kategori tinggi, 32% pada kategori sedang, dan 28% pada kategori rendah. Siswa di kategori tinggi mampu menghubungkan konsep dengan benda konkret di sekitar mereka dan menjelaskan sifat-sifat bangun datar dengan bahasa sendiri. Sementara itu, kendala utama pada siswa kategori rendah adalah kesulitan dalam memahami instruksi soal dan literasi matematis. Secara keseluruhan, mayoritas siswa (72%) telah mencapai pemahaman yang cukup hingga sangat baik dalam klasifikasi bangun datar. Kata kunci: Pemahaman Konseptual, Bangun Datar, Geometri, Sekolah Dasar, Klasifikasi.